2008
DOI: 10.1002/da.20358
|View full text |Cite
|
Sign up to set email alerts
|

Shame, personality, and social anxiety symptoms in Chinese and American nonclinical samples: a cross-cultural study

Abstract: Shame has been observed to play an important role in social anxiety in China [Xu, 1982]. Shame and personality factors, such as neuroticism and introversion-extraversion, are also related to social anxiety symptoms in Chinese college students [Li et al., 2003]. The aim of this study was to explore cross-cultural differences of the effects of shame and personality on social anxiety using the Experience Scale of Shame, the Eysenck Personality Questionnaire-Revised Short Scale and Social Anxiety Inventory. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 37 publications
5
49
1
2
Order By: Relevance
“…Third, the present study did not take into account the relationship between worry and related constructs such as "shame or executive shyness" in China. Zhong et al(2008) found that shame is a mediator between the personality and social anxiety symptoms in a Chinese college sample, while shame did not play the same role in the American sample. Thus, the convergence and divergence between worry and shame should be investigated in a follow-up study in China.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Third, the present study did not take into account the relationship between worry and related constructs such as "shame or executive shyness" in China. Zhong et al(2008) found that shame is a mediator between the personality and social anxiety symptoms in a Chinese college sample, while shame did not play the same role in the American sample. Thus, the convergence and divergence between worry and shame should be investigated in a follow-up study in China.…”
Section: Discussionmentioning
confidence: 77%
“…Unlike EFA, CFA can evaluate different competing structure models and place restrictions on various parameter estimates such as factor loadings and variances, thereby resulting in a more parsimonious model (Wang, 1999;Zhong et al, 2008). The CFA model can be identified when the number of measured variables exceeds the number of freely estimated parameters, and the correlation of errors can be calculated and specified among the indicator residuals to reflect the method effects due to the similarity of items outside of factor loading, such as overlapped content, similar phrasings, and other susceptibilities to demand characteristics (Brown, 2003;Hau, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Although in the last decades a decrease in birth-rate was observed, leading to a large amount of family with only one child, there is not such a restrictive policy in Italy and the number of children is mainly a private decision (ISTAT 2014). In addition, as suggested by past research concerning Chinese adolescents, higher levels of anxiety may be affected by Taijin Kyofusho (fear of interpersonal relations), a collectivistic culturally specific fear of offending others with inappropriate attitudes, behaviors or offensive appearances (Cohen et al 2013;Kirmayer 1991;Nakamura et al 2002;Zhong et al 2008). Feelings of anxiety, fear, shame, embarrassment, exclusion and rejection by others are often experienced by people who are suffering from this syndrome (Lim 2013).…”
Section: Discussionmentioning
confidence: 87%
“…We also omitted three items of the ''Embarrassment'' subscale because they do not seem to reflect this emotion precisely; this doubt was also expressed in a previous study [4]. The sentiment of embarrassment would depend on cultural norms of ''embarrassment'' and ''shame'', which are known to be quite diverse across cultures, [13,14], and it was well beyond the scope of this study to develop items universally applicable to different cultural backgrounds on this theme.…”
Section: Scale Item Selectionmentioning
confidence: 92%